Kapasitor MOS dengan dielektrik Ceria Amorf - Khairurrijal Khairurrijal; Darsikin Darsikin; Maman Budiman (Institut Teknologi Bandung, 2004)
Amorphous ceria (CeO2) thin films were deposited on a silicon (100) substrate by using a pulsed-laser ablation deposition (PLAD) technique. The substrate temperature was varied from 600 to 7000 C and the ambient was a pure oxygen gas at the pressure of 100 mTorr. It was found that the growth rate is 17.5 nm/min. Low fixed-charge densities (1011/cm2) and high resistivies (109-1012 Î© cm) of the CeO2 thin films indicate that the films could be used for oxide layer of metal-oxide-semiconductor (MOS) capacitors. Electron conduction mechanism in the CeO2 thin films is ohmic at voltages below 1 V while that at voltages above 1 V are due to quantum tunneling process.